A role for TET2 in parathyroid carcinoma. Issue 7 (July 2017) - Barazeghi, Elham; Gill, Anthony J; Sidhu, Stan; Norlén, Olov; Dina, Roberto; Palazzo, F Fausto; Hellman, Per; Stålberg, Peter; Westin, Gunnar
Abstract : Primary hyperparathyroidism (pHPT) is rarely caused by parathyroid carcinoma (PC, <1–5% of pHPT cases). The TET proteins oxidize the epigenetic mark 5-methylcytosine to 5-hydroxymethylcytosine (5hmC) and inactivation by mutation or epigenetic deregulation of TET1 and TET2 play important roles in various cancers. Recently, we found that 5hmC was severely reduced in all of the analyzed PCs and with deranged expression of TET1 for the majority of PCs. Here, we have examined the expression of the TET2 protein in 15 5hmC-negative PCs from patients who had local invasion or metastases. Cell growth and cell migratory roles for TET2 as well as epigenetic deregulated expression were addressed. Immunohistochemistry revealed very low/undetectable expression of TET2 in all PCs and verified for two PCs that were available for western blotting analysis. Knockdown of TET2 in the parathyroid cell line sHPT-1 resulted in increased cell growth and increased cell migration. DNA sequencing of TET2 in PCs revealed two common variants and no obvious inactivating mutations. Quantitative bisulfite pyrosequencing analysis of the TET2 promoter CpG island revealed higher CpG methylation level in the PCs compared to that in normal tissues and treatment of a PC primary cell culture with the DNA methylation inhibitor 5-aza-2′-deoxycytidine caused increased expression of the methylated TET2 gene. Hence, the data suggest that deregulated expression of TET2 by DNA hypermethylation may contribute to the aberrantly low level of 5hmC in PCs and further that TET2 plays a cell growth and cell migratory regulatory role and may constitute a parathyroid tumor suppressor gene.